2019
DOI: 10.1038/s41598-019-50147-7
|View full text |Cite
|
Sign up to set email alerts
|

A causal study of the phenomenon of ultrasound neurostimulation applied to an in vivo invertebrate nervous model

Abstract: Focused ultrasound are considered to be a promising tool for the treatment of neurological conditions, overcoming the limitations of current neurostimulation techniques in terms of spatial resolution and invasiveness. Much evidence to support the feasibility of ultrasound activation of neurons at the systemic level has already been provided, but to this day, the biophysical mechanisms underlying ultrasound neurostimulation are still widely unknown. In order to be able to establish a clear and robust causality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Further studies have confirmed that low-intensity focused ultrasound (LIFU) activates neurocircuits in both model organisms and humans. Indeed, pulsed focused ultrasonic stimulation has been shown to effectively induce nerve responses and action potentials in the giant fibers of invertebrate animals [ 14 , 15 ]. Moreover, precise stimulation of the deep brain nuclei and modulation of brain neuronal activity [ 16 19 ] have been shown to induce muscle contraction of the limbs of rats and rabbits, as verified by electromyography (EMG) [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have confirmed that low-intensity focused ultrasound (LIFU) activates neurocircuits in both model organisms and humans. Indeed, pulsed focused ultrasonic stimulation has been shown to effectively induce nerve responses and action potentials in the giant fibers of invertebrate animals [ 14 , 15 ]. Moreover, precise stimulation of the deep brain nuclei and modulation of brain neuronal activity [ 16 19 ] have been shown to induce muscle contraction of the limbs of rats and rabbits, as verified by electromyography (EMG) [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, low‐intensity applications of US have been increasingly explored for safe and efficient stimulation and modulation of cellular activity 15–17 . Though much of the work in this field has been focused on applications for neurostimulation/neuromodulation, 18,19 US can also be used to regulate the activity of other excitable cells such as pancreatic endocrine cells 15,20,21 …”
mentioning
confidence: 99%
“…Where N is the number of transducers of a squared 2D phased array. To avoid grating lobes in the field of view of the transducer array, d must respect the condition given by (2), where θmax is the maximum of θXZ and θYZ [30]. For θmax of ±90°, d has a minimum value at λ/2.…”
Section: System Designmentioning
confidence: 99%
“…EVERAGING decades of technological advances in the field of ultrasound medical diagnostic imaging, new ultrasound biomedical applications are now emerging, such as ultrasound neuromodulation [1][2][3][4][5][6] and ultrasonic power delivery and communication for medical implants [7][8][9][10][11][12][13][14]. These applications benefit from the attractive properties of ultrasound energy propagation and interaction with tissue, such as low scattering, low attenuation, and safe energy levels.…”
Section: Introductionmentioning
confidence: 99%